Gravidity, contraceptive use and acceptability of a proposed three-baby policy in a municipality of Ghana - Ametefe, Vivian; Appiah-Brempong, Emmanuel; Okyere, Paul; Vampere, Hasehni; Obeng Nyarko, Gloria; Aggrey, Priscilla Aba; Dadzie Mintah, Francis (International Journal Of Community Medicine And Public Health, 2022)
Background: Childbirth and high total fertility rate among women is traditionally held in high esteem in many African societies. However, the menace of large families and increasing populations has triggered both global and National actions towards population control. This study determined the factors associated with gravidity, the acceptability of a proposed three-baby per couple policy and the prevalence of modern contraceptives in a Ghanaian municipality. Methods: A descriptive cross-sectional study design was adopted and involved 350 women of reproductive age who had a history of past or present pregnancy. Data were collected using a structured questionnaire and analysed using descriptive and inferential statistical analysis with the aid of STATA version 14. Results: The results indicated that 97.39% of the participants had knowledge of modern contraceptives and 33.91% were current users of modern contraceptives. Gravidity showed significant association with age, marital status, educational level, employment status and source of contraceptive (p<0.001). Participants with no formal education had the highest gravidity (Mean±SD=6.0±1.7). Also, 86.29% were aware of the proposed three-baby policy but only 28.37% were willing to accept the policy. A linear regression analysis showed a negative association between age and gravidity (p=0.018; β=-0.008). The participants’ desired number of children was also statistically significant with gravidity (p<0.001). Conclusions: Efforts towards population control can be challenging due to the low use of modern contraceptives which is effective in reducing the TFR. Also the low acceptability of the proposed three-baby policy amongst reproductive women suggest their desire for more children.